Composition and diversity of bacteria from giant Asian honeybee Apis dorsata gut - Nurdjannah Jane Niode; ARYANI ADJI; JIMMY RIMBING; MAX TULUNG; Trina Ekawati Tallei (Society for Indonesian Biodiversity, 2021)
Abstract. Niode NJ, Adji A, Rimbing J, Tulung M, Tallei TE. 2021. Composition and diversity of bacteria from giant Asian honeybee Apis dorsata gut. Biodiversitas 22: 906-912. As a social insect, honeybee possesses a unique gut bacteria community. Therefore, we need to understand the composition and diversity of bacteria in Apis dorsata gut, the largest honeybee species that live in the forest, especially in Southeast Asia. The present study aimed to investigate the gut bacteria of A. dorsata using a metabarcoding approach. The DNA barcode region used in this approach was the V3-V4 region of 16S rRNA. Honeybees were caught in a forest area located in Tareran, South Minahasa, North Sulawesi, Indonesia. There were 11 phyla identified from the gut of A. dorsata. The most abundant phyla were Firmicutes (95.8%), Proteobacteria (3.7%), and Actinobacteria (0.4%). The class Bacilli was responsible for 94.5% of the total bacterial population, the dominant family was Bacillaceae (87.2%), and the dominant genus was Bacillus (87%). Simpson (1-D) 0.24 and Shannon diversity index 0.98 indicated that the diversity of the genera was low. A nonsignificant number of species belong to the lactic acid bacteria was also detected, which may have certain benefits that need to be investigated further.